Fish behavior based on the effect of variations in oceanographic condition variations in FADs Area of Bone Bay Waters, Sulawesi, Indonesia - Arham Rumpa; Najamuddin Najamuddin; Safruddin Safruddin; Muhammad Abduh Ibnu Hajar (Society for Indonesian Biodiversity, 2022)
Abstract. Rumpa A, Najamuddin, Safruddin, Hajar MAI. 2022. Fish behavior based on the effect of variations in oceanographic condition variations in FADs Area of Bone Bay Waters, Sulawesi, Indonesia. Biodiversitas 23: 1875-1883. Fish behavior is the response of fish to conditions existing in their environment. One of the causes is oceanographic factors, which can affect the schooling movement of fish. This study aimed to identify the schooling behavior of fish based on the influence of oceanographic variations in the Fish Aggregating Device (FADs) area. Study took place from March to September 2021 in Bone Bay Waters, Indonesia. The type of research was experimental fishing with an acoustic approach for 57 times. Parameters observed were current velocity, current direction, and water temperature to the distance of schooling fish from FADs vertically and horizontally in the afternoon, evening, night, and early morning. The behavioral data of fish species were namely Decapterus russelli. The results showed namely the variation in current velocity affected the horizontal distance; variation in the direction of currents affected the horizontal distribution distance, while the water temperature affected the vertical schooling of fish. In the operation of fishing gear, especially in the early morning, in terms of the concentration pattern of schooling fish under FADs. The ideal current velocity was in the range of 0.2-0.29 [m s-1], while the ideal current direction is direct current was at the angle of 0°-60°. The schooling of fish approached to the surface and was concentrated under FADs at >30°C. Understanding on the distribution of horizontal and vertical movements and the time of concentration of fish schooling at the central point of FADs due to oceanographic variations will facilitate the effectiveness of fishing gear operation.